Financial analysis of Rubber Plantation and Cattle Production A Case Study in Poungpao Village, Phonxay District, Luangprabang Province - NAOYENG, Khamkeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
This study has been analyzed of the economic benefits between rubber and cattle investments in Poungpao Village, Phonxay District, Luangprabang Province. The main objectives are focused on analyzing productivity and financial returns of rubber plantation and cattle raising investments by using a sampling land area of 1 hectare analyzing for each product study. The research methodology has reviewed for all related documents and included field data collection at the study site. The field data collection were also included of local communities and household interview, especially for the households who have planted rubber in the Village for 61 families (interviewed 100 percent in the village) and the households who raised cattle in the village is 58 households and these were all interviewed (100 percent). Field data collection was asked deeply for the local people’s problems facing and recommendation. The results of study has shown that in the period of 25 years of the plantation rubber investment, the highest of benefit return or maximum profit is 99,132,360 Kip/ha, and the total benefit return from cattle investment is 98,933,000 Kip/ha. The analysis showed that the rubber plantation investment has higher of financial return compared to cattle investment. However, if assuming that interest of capital loaning is 17.83% per year for rubber plantation investment, the investment is not profitable and it would highly recommend and it is not suitable for investment in the future. For cattle investment, if the interest of capital loaning is 15.42% per year, the investment is not profitable and it would highly recommend and it is not suitable for investment in the future. The result analyzed has indicated that the weakness points of plantation and cattle investments will profitable and succeed, if the interest rate of capital loaning is lower or below than 14.24% per year for rubber plantation investment and 12.16% of cattle investment. The analysis of problem and the potential of rubber plantation investment shown that the problems were mostly happened at the starting time of rubber plantation and also happened at harvesting rubber products time. It is because of local people are lacking of capital investment for the beginning time and they also need more skills and techniques of rubber tapping and processing. The potential and advantage points for rubber plantation investment are based on hard working and interesting investment of rubber plantation investment.